2006
DOI: 10.1093/jn/136.3.861s
|View full text |Cite
|
Sign up to set email alerts
|

Aged Garlic Extract Protects against Methotrexate-Induced Apoptotic Cell Injury of IEC-6 Cells

Abstract: Gastrointestinal toxicity is one of the most serious side effects of methotrexate (MTX) treatment. The side effects often disrupt the cancer chemotherapy. We previously reported that aged garlic extract (AGE) protects the small intestine of rats from MTX-induced damage. In this study, the protection of AGE against MTX-induced damage of IEC-6 cells originating from the rat jejunum crypt was investigated. MTX decreased the viability of IEC-6 cells, but this effect was prevented by AGE (0.5%). The MTX-induced apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…In contrast, in the MMTX group there were only a few necrotic cells. Previous studies have also shown that methotrexate intensifies apoptosis 23 . Caspase is a gene that controls cell apoptosis.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, in the MMTX group there were only a few necrotic cells. Previous studies have also shown that methotrexate intensifies apoptosis 23 . Caspase is a gene that controls cell apoptosis.…”
Section: Discussionmentioning
confidence: 95%
“…13,32 5-FU inhibited normal intestinal cell proliferation and reduced villus height in rats, 30 while Methotrexate (MTX), another anti-metabolite chemotherapy drug, has been shown to decrease viability and induce apoptosis in IEC-6 cells. 33 Smaller PAs (3-7mers) are thought to not cross the intestinal barrier and remain bioactive in the gut. 34 Erlejman et al 34 demonstrated that hexameric procyanidins were most effective in preventing oxidative damage in Caco-2 colonic cells.…”
Section: Discussionmentioning
confidence: 99%
“…GSE represents a readily available source of polyphenols, which is particularly rich in PAs. 21 In the current study, IEC-6 cells were used in an in vitro assay of normal intestinal cell 5-FU damage as they are non-malignant intestinal cells derived from rat ileum 33 and have been previously used to study gastrointestinal toxicity such as that induced by MTX. 33 Exposure of IEC-6 cells to 5-FU greatly reduced IEC-6 cell viability relative to non-damaged control cells, as measured by neutral red assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IEC-6 cells have the characteristics of crypttype intestinal cells and have been extensively used as an in vitro intestinal model for gastrointestinal regeneration (Horie et al, 2006;Santos et al, 1997). In the present study, the SM extracts induce extracellular Ca 2 þ entry and massive intracellular Ca 2 þ release in Ca 2 þ -contained medium, and induce intracellular Ca 2 þ release in Ca 2 þ -free medium.…”
Section: Discussionmentioning
confidence: 65%